Surgical and clinical determinants of postoperative Hirschsprung‐associated enterocolitis: Multivariate analysis in a large cohort - Guoyong Wang; Kai Gao; Rensen Zhang; Qianyang Liu; Cailong Kang; Chunbao Guo (Wiley, 2024)
Abstract This research meticulously explores the diverse factors influencing the occurrence of Hirschsprung‐associated enterocolitis (HAEC) subsequent to surgical interventions for congenital megacolon. Considering that Hirschsprung's Disease (HSCR) management predominantly necessitates excision of the aganglionic intestinal segment, the study specifically delineates the correlation between the extent of the excised intestinal segment and the HAEC risk post‐surgery. An analysis of clinical data from 505 patients spanning 2012-2022 enabled a comparison of clinical attributes between patients with and without postoperative HAEC, the application of statistical analyses to identify factors significantly correlating with HAEC, and the determination of independent risk factors via a Logistic regression model. Findings indicate a significant association between preoperative conditions, HSCR variants, and the excised intestinal segment's length with HAEC risk, identifying resection length and albumin levels as independent risk factors. Notably, an increase in resection length by 1 cm correlates with a 9.8% rise in postoperative HAEC risk, whereas a 1 g/L elevation in albumin levels corresponds to a 5.6% risk reduction. Subgroup analyses reaffirm that, across all HSCR variants, an extended resection length significantly elevates HAEC risk. This study underscores the critical roles of albumin levels and the length of the resected intestinal segment as independent risk factors for HAEC post‐congenital megacolon surgery, providing essential insights for clinical strategies aimed at mitigating HAEC risk and enhancing patient care outcomes.